"Hyperledger" versus "hyperscaler"? Can coopetition on decentralized platforms be a countervailing power to big tech? Platform capitalism between new and old forms power - Ulrich Klüh (Hochschule Darmstadt, Fachbereich Wirtschaft, Zentrum für Nachhaltige Wirtschafts- und Unternehmenspolitik ZNWU, 2025)
We collect observations on how power constitutes itself in decentralized digital platform constellations that position themselves as alternatives to platforms operated by big tech (which we coin "hyperledgers"). We then compare these forms of power to the incumbent structures, the so called "hyperscalers". Such a comparison yields new insights into the way power "works" in surveillance-based platform capitalism. The crucial insight of our analysis is that it is highly unlikely that platform alternatives can be scaled up decisively within the current capitalist accumulation regime. Instead of focusing on finding business models within this regime, platform alternatives should therefore strive for regime change. This, however, would require new alliances, in particular between the victims of surveillance (workers and consumers) and the platform alternatives. The latter, in turn, would not only require massive public funding, but also support from civil society actors representing workers (i.e. unions) to be able to compete with incumbent hyperscalers.
Keywords: 330; Power relations; platform and surveillance capitalism; entrepreneurial activism; organizing studies; labor relations; democratization